An Extended Interval-Valued Pythagorean Fuzzy VIKOR Approach With Logarithmic Distance Measures for Service Quality Evaluation of University Library - Zhengfu Yu; Donglai Wang; Azleena Mohd Kassim; Sijia Zhu; Zhe Liu (Journal of Mathematics)
Evaluating service quality presents a multicriteria decision-making (MCDM) challenge, involving numerous factors that contribute to its complexity. Traditional approaches to assessing service quality frequently struggle to encapsulate the ambiguity and uncertainty in user experiences, particularly when confronted with intricate, multidimensional indicators of service quality. In this paper, we introduce two novel distance measures based on logarithmic function for interval-valued Pythagorean fuzzy sets (IVPFSs). The important properties of the new measure are not only proved but also verified by numerical examples. On this basis, the VlseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR) method is extended to the interval-valued Pythagorean fuzzy environment to evaluate the service quality of university libraries. The research results show that the proposed method has significant results in improving the accuracy of evaluation and coping with complex index systems. Finally, comparative analysis and sensitivity analysis are carried out. The results of these analyses further validate the effectiveness of the proposed method, which provides a new and more reliable way for service quality evaluation.